Rationale for construction vibration for drying granular and granular materials - Зозуляк, Ігор Анатолійович (Eastern-European Journal of Enterprise Technologies, 2014)
Various processing methods are used to bring grain to a steady state for storage, provide quantitative and qualitative grain characteristics, the most effective of which is grain drying. The results of experimental studies of vibration drying and industrial equipment operation experience showed the following benefits of using vibrations in drying dispersed materials: intensive mixing of material particles, intensive moisture removal due to constant renewal of moisture exchange surface, material temperature equalization in the bulk of drying apparatus, drying quality improvement, decrease in the vibro-pseudo-liquefaction startup speed, energy costs reduction, possibility of combining various manufacturing operations at continuous process running (transportation and drying, granulation and drying, shell formation and drying, fractionation and drying, etc.), creation of new highly-efficient vibration dryers with adjustable vibration settings. Having analyzed some types of vibration dryers it was decided to develop the design solution of the dryer for granulated and granular materials with high and controllable heat-mass transfer intensity. The proposed design solution allows simultaneously implement two controlled drying processes for heat-mass transfer intensification during drying bulk materials. There is intense moisture evaporation from the upper layers of granulated and granular materials due to the imposition of a temperature gradient on the controlled vibration mixing and motion (realized by bulk material displacement) along the section of U-like body in the first section of U-like vibration machine body. The moisture, remained in the central layers of granulated and granular materials in the second section of U-like vibration machine body at controlled mixing and motion of bulk material along the section of U-like body is intensively removed by convective drying method using the hollow branch pipe with gas-distributing holes.